2021
DOI: 10.4236/fns.2021.121007
|View full text |Cite
|
Sign up to set email alerts
|

A Smart Fluorescent Light Spectroscope to Identify the Pork Adulteration for Halal Authentication

Abstract: The complication of adulterated ingredients in processed food items is widely observed in the food industry and remains a continuous disquiet for end users. This problem may affect consumers' spiritual beliefs, likewise with their fitness and diet. Hence commercial foods should be scrutinized for the precision of the avowed ingredients. This study is dedicated to developing a Fluorescent light Spectroscope to identify the pork adulteration. A simple way of DNA extraction process has been introduced to make the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Electromagnetic spectroscopy, which studies the fluorescence of a material, can explain a beam of light (usually visible light) emitted by electrons in the molecules of the material [ 174 ]. Fluorescence is the emission of light that occurs within nanoseconds of the absorption of light with a shorter wavelength.…”
Section: Detection Methods For Authentication and Adulteration Of Hal...mentioning
confidence: 99%
See 1 more Smart Citation
“…Electromagnetic spectroscopy, which studies the fluorescence of a material, can explain a beam of light (usually visible light) emitted by electrons in the molecules of the material [ 174 ]. Fluorescence is the emission of light that occurs within nanoseconds of the absorption of light with a shorter wavelength.…”
Section: Detection Methods For Authentication and Adulteration Of Hal...mentioning
confidence: 99%
“…In this experiment, different mixtures of foods (with and without pork) were examined and the light spectrum was measured using RSpec software. The results showed that fluorescence spectroscopy could distinguish pure pork, a mixture with pork, and without pork [ 174 ]. Munir et al (2019) used the FTIR spectrum technique in combination with a partial least squares (PLS) method for the rapid detection of lard in sunflower, canola, coconut, olive, and mustard oils.…”
Section: Detection Methods For Authentication and Adulteration Of Hal...mentioning
confidence: 99%
“…Furthermore, the amalgamation of artificial intelligence (AI), chemometrics, and the Internet of Things (IoT) with these advanced methods can augment the precision, velocity, and potential of multiplexed analyte detection (Ng et al, 2022). For instance, a study by Islam et al (2021) focuses on the fundamental methods of constructing an intelligent fluorescence spectroscope apparatus coupled with a straightforward DNA extraction protocol crucial in detecting pork contamination in food and beverage samples. The spectroscope was utilised to observe various material combinations, including those with and without pork, and subsequently measure their respective light spectra using RSpec software.…”
Section: Technological Advances In Halal Ingredients Analysismentioning
confidence: 99%
“…As a result, effective methods are necessary for assuring the meat industry’s proper development, and rapid, comprehensive, accurate, and reliable detection technologies are crucial to achieving this goal. One approach for guaranteeing food authenticity could be metabolomic and lipidomic technology ( Ali et al, 2020b ; El Sheikha et al, 2017 ; Islam et al, 2021 ; Vanany et al, 2020 ) compared to existing methods such as polymerase chain reaction (PCR), which has the limitation of being easily degraded in processed foods so that it has the potential to cause false negatives ( Jannat et al, 2018 ; Jannat et al, 2020 ; Lubis et al, 2016 ). Metabolomic as method with high accuracy, comprehensive analysis of the whole metabolome which refer to the full complement of small molecule, while lipidomic explored area within lipid analytics and more specifically meat adulteration, so this method can used authentication of meat product ( Emwas et al, 2019 ; Trivedi et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, effective methods are necessary for assuring the meat industry's proper development, and rapid, comprehensive, accurate, and reliable detection technologies are crucial to achieving this goal. One approach for guaranteeing food authenticity could be metabolomic and lipidomic technology (Ali et al, 2020b;El Sheikha et al, 2017;Islam et al, 2021;Vanany et al, 2020) compared to existing methods such as polymerase chain reaction (PCR), which has the limitation of being easily degraded in processed foods so that it has the potential to cause false negatives (Jannat et al, 2018;Jannat et al, 2020;Lubis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%